Prevalence, incidence, and outcome of non-alcoholic fatty liver disease in Asia, 1999–2019: a systematic review and meta-analysis. (May 2019) - Li, Jie; Zou, Biyao; Yeo, Yee Hui; Feng, Yuemin; Xie, Xiaoyu; Lee, Dong Hyun; Fujii, Hideki; Wu, Yuankai; Kam, Leslie Y; Ji, Fanpu; Li, Xiaohe; Chien, Nicholas; et al.
Summary: Background: Non-alcoholic fatty liver disease (NAFLD) is the most prevalent chronic liver disease worldwide. Asia is a large, heterogeneous area with substantial variation in socioeconomic status and prevalence of obesity. We estimated the prevalence, incidence, and outcomes of NAFLD in the Asian population to assist stakeholders in understanding NAFLD disease burden. Methods: We searched PubMed, EMBASE, and the Cochrane Library from database inception to Jan 17, 2019, for studies reporting NAFLD prevalence, incidence, or outcome in Asia. We included only cross-sectional and longitudinal observational studies of patients with NAFLD diagnosed by imaging, serum-based indices, or liver biopsy. Studies that included patients with overlapping liver disease or that did not screen for excess alcohol consumption were excluded. Two investigators independently screened and extracted data. The main outcomes were pooled NAFLD prevalence, incidence, and hepatocellular carcinoma incidence and overall mortality in patients with NAFLD. Summary estimates were calculated using a random-effects model. This study is registered with PROSPERO, number CRD42018088468. Findings: Of 4995 records identified, 237 studies (13 044 518 participants) were included for analysis. The overall prevalence of NAFLD regardless of diagnostic method was 29·62% (95% CI 28·13–31·15). NAFLD prevalence increased significantly over time (25·28% [22·42–28·37] between 1999 and 2005, 28·46% [26·70–30·29] between 2006 and 2011, and 33·90% [31·74–36·12] between 2012 and 2017; p<0·0001). The pooled annual NAFLD incidence rate was 50·9 cases per 1000 person-years (95% CI 44·8–57·4). In patients with NAFLD, the annual incidence of hepatocellular carcinoma was 1·8 cases per 1000 person-years (0·8–3·1) and overall mortality rate was 5·3 deaths per 1000 person-years (1·5–11·4). Interpretation: NAFLD prevalence in Asia is increasing and is associated with poor outcomes including hepatocellular carcinoma and death. Targeted public health strategies must be developed in Asia to target the drivers of this rising epidemic and its associated complications, especially in high-risk groups, such as older obese men. Funding: None.